Is TOR1A a risk factor in adult‐onset primary torsion dystonia?. Issue 6 (4th March 2013) - Groen, Justus L.; Ritz, Katja; Tanck, Michael W.; van de, Bart P.; van, Jacobus J.; Aramideh, Majid; Baas, Frank; Tijssen, Marina A. J.
<x xml:space="preserve">Abstract</x> Background Studies of genetic association between TOR1A and adult‐onset primary torsion dystonia have contradictory results. Methods The authors genotyped TOR1A single nucleotide polymorphisms rs1801968, rs2296793, rs1182 and rs3842225 in a cohort of clinically well characterized cervical dystonia patients (n=367) and constructed haplotypes. The authors systematically reviewed the published case‐control TOR1A association studies in adult‐onset primary torsion dystonia. Results In this Dutch cervical dystonia cohort, no significant association was found with TOR1A variants. In the meta‐analysis (eight studies, 1332 adult‐onset primary dystonia patients) no variant reached overall significance. However, in a selection of familial cases the functional variant p.Asp216His (rs1801968) was associated with increased dystonia risk (odds ratio 1.43; 95%CI 1.01–2.02). Conclusions Meta‐analysis does not show association with common variants in TOR1A in adult‐onset primary dystonia, except for the functional variant rs1801968 in familial focal dystonia cases. © 2013 Movement Disorder Society